Effectiveness of resin infiltration (ICON) and microabrasion-remineralization technique with two remineralizing agents (Tooth Mousse and Toothmin) on permanent incisor hypoplasia - A randomized clinical trial - Yash Shah; Anshula Deshpande; Aishwarya Jain; Vidhi Jaiswal; Mudra Andharia (Wolters Kluwer Medknow Publications, 2023)
Aims: The study aims to compare the effect of resin infiltration and microabrasion-remineralization (MAb-Re) with Tooth Mousse and Toothmin on permanent incisor hypoplasia. Materials and Methods: The study included children with permanent incisor hypoplasia above 9 years of age, 171 teeth divided randomly into four groups: Group A - ICON, Group B - MAb-Re using Tooth Mousse, Group C - MAb-Re using Toothmin, and Group D - control group. Process involved taking standardized photographs at T1 - before intervention, T2 - immediately after treatment, and T3 - 6-month follow-up. Color evaluation, area calculation, participant and expert opinion using a Likert scale, treatment time, and cost-effectiveness were all taken into consideration during the assessment. Statistical Analysis Used: Data were collected, entered into a computer, and analyzed; one-way ANOVA was used for intergroup assessment. Results: Overall color change was evident immediately after treatment in the ICON group compared to other groups (P < 0.05). However, no significant difference in color change was visible between the groups after 6 months. Reduction in hypoplastic area was seen in all the groups. The mean time was similar for all the groups. Toothmin was found to be the most cost-effective in comparison with the other two interventions. Conclusions: ICON proved to be more effective immediately after treatment for masking incisor hypoplasia. However, at 6-month follow-up interval, all the groups gave similar results.